2005
DOI: 10.1099/mic.0.27739-0
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype switching affects biofilm formation by Candida parapsilosis

Abstract: Generation of biofilms by the pathogenic yeast Candida parapsilosis is correlated closely with disease. The phenomenon of phenotype switching in 20 isolates of C. parapsilosis was examined and the relationship with biofilm development was investigated. Four stable and heritable phenotypes were identified -crepe, concentric, smooth and crater. Cells from crepe and concentric phenotypes are almost entirely pseudohyphal, whilst cells from smooth and crater phenotypes are mostly yeast-like. The pseudohyphae from c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
94
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(109 citation statements)
references
References 49 publications
(50 reference statements)
12
94
0
3
Order By: Relevance
“…In contrast to Candida albicans and Candida parapsilosis [17,18], the smooth phenotype of C. neoformans exhibited the highest degree of both adhesion and biofilm formation. Biofilm formation was significantly higher than biofilm formation of mucoid and wrinkled switch variants of C. neoformans, suggesting that its superior biofilmforming capability is at least in part a result of its higher ability to adhere to polystyrene.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Candida albicans and Candida parapsilosis [17,18], the smooth phenotype of C. neoformans exhibited the highest degree of both adhesion and biofilm formation. Biofilm formation was significantly higher than biofilm formation of mucoid and wrinkled switch variants of C. neoformans, suggesting that its superior biofilmforming capability is at least in part a result of its higher ability to adhere to polystyrene.…”
Section: Discussionmentioning
confidence: 99%
“…The average Pz values -the ratio between the colony diameter (dc) and dc plus precipitation zone (dcp) -were calculated and the isolates were grouped into five categories according to their Pz values 9 . All biofilm assays were conducted 10 times for each isolate 10 . The isolates were classified into four categories: non-producers, weak, moderate, or strong biofilm producers 4 C. orthopsilosis are not usually found or occur at very low frequencies in nosocomial environments; previous reports have suggested they are associated mainly with clinical samples and that their relative frequency varies among hospitals and geographic regions 11,12 .…”
mentioning
confidence: 99%
“…Concerning NCAC species, C. parapsilosis distinct switch phenotypes exhibited differential ability to form biofilm on polystyrene surfaces (Laffey and Butler, 2005). For C. tropicalis, França et al (2010) also found a correlation in phenotypic switching and biofilm formation.…”
Section: Switching Morphotypes: Ultrastructure and Morphological Typesmentioning
confidence: 89%